THE EFFECT OF APPLYING SENTENCE COMBINING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Rismawati and Siti Aisyah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study aims to discover the effect of applying sentence Combining Technique on students’ achievement in writing descriptive text. It was conducted by using experimental research design. The population of this research was the eight (VIII) grade students of SMP Swasta Prayatna Medan with eight parallel classes. The samples of the research were 20% of the totaling number of students divided into two groups, experimental and control group which were chosen by using random sampling technique. Seventy two students were taken as the samples. The experimental group was taught by using Sentence Combining Technique, while the control group was taught by using conventional teaching. The instrument for collecting the data was a writing test. Pearson Product Moment formula was applied to obtain the reliability of the test. Based on the calculation, it shows that the reliability of the test was 0.86 categorized as high reliability. Then, after analyzing the data, it was found that the value of tobserved was 5.57 with the degree of freedom (df)=70 at the level of significance (α = 0.05). It means that tobserved is higher than ttable (5.57 > 1.67). The result of this study shows that Sentence Combining Technique has a significant effect on students’ achievement in writing descriptive text.